Битва Деревьев: фантастический роман / И. Новак - Новак Илья (Герои уничтоженных империй, 2006)
Экземпляры: аб. ЦБ (20230925) / Инвентарный номер: 17288 / Цена: / Сис.шифр: 84(2)6 / Авт.знак: Н 72 / ББК: 84(2)6